Sweet tea (Lithocarpus polystachyus rehd.) as a new natural source of bioactive dihydrochalcones with multiple health benefits - Shang, Ao; Liu, Hong-Yan; Luo, Min; Xia, Yu; Yang, Xiao; Li, Hang-Yu; Wu, Ding-Tao; Sun, Quancai; Geng, Fang; Gan, Ren-You (Critical reviews in food science and nutrition, 2022)
Sweet tea (Lithocarpus polystachyus Rehd.) has been consumed as herbal tea to prevent and manage diabetes for a long time. Recent studies indicate that sweet tea is rich in a variety of bioactive compounds, especially a class of nonclassical flavonoids, dihydrochalcones. In order to provide a better understanding of sweet tea and its main dihydrochalcones on human health, this review mainly summarizes related literature in the recent ten years, with the potential molecular mechanisms emphatically discussed. Phlorizin, phloretin, and trilobatin, three natural sweeteners, are the main dihydrochalcones in sweet tea. In addition, sweet tea and its dihydrochalcones exhibit plenty of health benefits, such as antioxidant, anti-inflammatory, antimicrobial, cardioprotective, hepatoprotective, antidiabetic, and anticancer effects, which are associated with the regulation of different molecular targets and signaling pathways. Therefore, sweet tea, as a rare natural source of dihydrochalcones, can be processed and developed into nutraceuticals or functional foods, with the potential application in the prevention and management of certain chronic diseases.